Diffusion-induced grain boundary migration as mechanism for grain growth and defect annihilation in chalcopyrite thin films. (1st June 2016) - Stange, Helena; Brunken, Stephan; Greiner, Dieter; Heinemann, Marc-Daniel; Kaufmann, Christian Alexander; Schmidt, Sebastian Simon; Bäcker, Jan-Peter; Klaus, Manuela; Genzel, Christoph; Mainz, Roland
Abstract: Polycrystalline thin-film solar cell absorbers exhibit complex structure-property relationships. Their microstructure is affected by sophisticated synthesis processes and influences the photovoltaic performance. In Cu(In, Ga)Se2 – currently presenting the highest efficiencies of all thin film absorber materials – the evolution of the [Cu]/([In] + [Ga]) ratio prior to the final Cu-poor composition is crucial for the efficiency of layers deposited by co-evaporation. A precise understanding of the effect of Cu on the microstructure is necessary to simplify the deposition process and bridge the gap between champion cell and module performance. In the present investigation, domain size growth, stacking fault annihilation and strain relaxation during low-temperature CuInSe2 co-evaporation are shown to correlate with Cu deposition, implying a driving force for grain growth induced by diffusion. Synchrotron based x-ray diffraction and fluorescence permit to study the microstructural evolution of the thin film in situ during Cu-Se deposition in a specially adapted process chamber. Repeated interruptions of the Cu evaporation reveal the dependency of the microstructure evolution on Cu deposition. Diffusion-induced grain boundary migration (DIGM) - hitherto not considered in chalcopyrite thin film deposition - is proposed as a mechanism by which Cu deposition drives grain growth at temperatures considerably below the threshold for thermal activation. Graphical abstract: